PELAKKSANAAN KURIKULUM DI SEKOLAH DASAR MILIK YAYASAN XAVERIUS PALEMBANG - Katarina Retno Triwidayati (Universitas PGRI Palembang, 2018)
ABSTRACTThe curriculum becomes one of the important things in the implementation of learning activities. This is because the curriculum contains the objectives to be achieved through learning activities. Changes in curriculum in Indonesia certainly need to be accompanied by understanding and implementation in school. This study describes theimplementation of the curriculum in elementary schools belonging to the Palembang Xaverius Foundation. This study is part of the research on the development of teaching materials and was carried out in six elementary schools under the auspices of the Palembang Xaverius Foundation in September 2016. The interviews were used to collect data and data analysis was carried out with reference to qualitative research procedures. The results showed that the six schools studied carried out the 2013Curriculum for one semester and continued with returning to the Education Unit Level Curriculum. in the year the research was carried out, the government determined to implement the 2013 Curriculum for several schools.Keyword: curriculum, elementary school, curriculum implementation